Entre poésie et politique - Gérard Raulet (Recherches Germaniques)
The topos of “Secret Germany” is a classic example of interdiscourse. The extremes can be illustrated by Alfred Bauemler and Johannes R. Becher. On January 18, 1930, the Reichsgründungstag, Baeumler gave under this title in Dresden a speech to the students of the Deutsche Studentengemeinschaft. It was published in 1934, when Baeumler had already become an important National Socialist official. At the other end of the political spectrum is a poem by the communist author Johannes R. Becher. First printed in 1942, it appeared in mid-1943 in his poetry collection Dank für Stalingrad. This draws attention to the fact that commitment to a secret Germany implies a gesture of resistance. In the name of another secret Germany, Hans and Sophie Scholl, the Stauffenberg brothers and other resistance fighters, nationalists and communists, sacrificed themselves. Because this ambivalence transforms secret Germany into an interdiscourse, I approach it in a strictly philological way, without being impressed by the prophetic tones that the motif of ‘poets and thinkers’ can take in poets and thinkers like George or Heidegger. In light of such a ‘positivist’ approach, discursive strategies form an almost undecipherable network of cross-references, so that discourses can only ever be measured in relation to each other—never according to ‘the letter’, let alone according to the truth or content of a work. After an overview, intended to circumscribe the thought pattern in its initial phase within George’s school, I try to reduce the complexity by placing Hölderlin at the center of the network, since the interpretation of Hölderlin’s patriotic hymns was from the beginning at the center of strategies.